Multistage Surgical Correction of Monocular Elevation Deficit with Large Angle Exotropia in a Pediatric Patient: A Case Report: Doi: 10.36351/pjo.v42i1.2250 - Surasmiati, Ni Made Ayu; Yuliawati, Putu; Widyasari, Putu Rima Adilitha; Oeiyano, Jelly Vianti Fransisca (Pakistan Journal of Ophthalmology, 2025)
Monocular elevation deficit (MED) is characterized by restricted upward gaze, often associated with hypotropia and horizontal deviation. We report the case of a young patient with right eye MED and large-angle exotropia. A negative forced duction test ruled out mechanical restriction. Surgical management was performed in three steps;partial Knapp operation combined with horizontal rectus recession and plication in the RE, followed by inferior rectus recession in the RE and horizontal rectus surgery in the contralateral eye, and finally ptosis correction. A multistage approach provided precise correction of ocular alignment and improved cosmesis. This case highlights the value of individualized, stepwise surgical planning for complex strabismus associated with MED and large horizontal deviations. Follow-up continued for 6 months after the final procedure, during which ocular alignment and eyelid position remained stable.